Aktifitas Antifungi Kitosan Hasil Hidrolisis Enzimatik Terhadap Penyakit Antraknosa (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2019)
Anthracnose disease caused by Colletotrichum gloeosporioides is one of an important fungal pathogen on mango fruits during the pre harvest or post harvest stage. The use of chitosan as an alternative method to control the disease is necessary due to its biodegradable, biocompatible and non-toxic effect. Chitosan tripolyphosphate (C-TPP) showed higher inhibition to C. gloeosporioides compared with that of low molecular weight (LMW) chitosan as affected by its particle size. The best of disease inhibitory activity was revealed by C-TPP B [0.2% LMW : 0.1% TPP; (5: 2)] and C [0.2% LMW: 0:08% TPP; (5: 1)] treatments based on Â in vitro and in vivo test. Because of the concentration of chitosan and TPP may affect to particle structure, hence the C-TPP formation needs further to be optimized so that the size is getting smaller and stable.